2016
DOI: 10.3746/pnf.2016.21.4.398
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Melanoidins Formed from Black Garlic after Different Thermal Processing Steps

Abstract: The objective of this study was to evaluate the characteristics of melanoidins formed from black garlic (BG) after different thermal processing steps. The melanoidins formed from BG during thermal processing were produced in large amounts, and the initial (280 nm), intermediate (360 nm), and final stage product (420 nm) had similar tendencies. Compounds like degraded proteins, peptides, and phenolic acids were present in the melanoidins during thermal processing. All the melanoidin samples showed different abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 31 publications
1
25
0
2
Order By: Relevance
“…The degree of browning was associated with the progression of the Maillard reaction, and the absorbance at 280, 320 to 360, and 420 to 450 nm corresponded to the products formed in the initial stage (sugar‐amine condensation and Amadori rearrangement), intermediate stage (sugar dehydration, fragmentation, and Strecker degradation), and final stage (aldol condensation, polymerization, and formation of heterocyclic nitro compounds) of the Maillard reaction, respectively (Nursten, ). Kang () found that the products yielded at the three stages followed similar tendencies, with a large number of intermediate products, along with compounds such as degraded proteins, peptides, and phenolic acids. The increased melanoidins gradually leads to darkening of garlic samples until dark brown or black color.…”
Section: Characteristic Components and Their Formation Mechanisms In Bgmentioning
confidence: 97%
“…The degree of browning was associated with the progression of the Maillard reaction, and the absorbance at 280, 320 to 360, and 420 to 450 nm corresponded to the products formed in the initial stage (sugar‐amine condensation and Amadori rearrangement), intermediate stage (sugar dehydration, fragmentation, and Strecker degradation), and final stage (aldol condensation, polymerization, and formation of heterocyclic nitro compounds) of the Maillard reaction, respectively (Nursten, ). Kang () found that the products yielded at the three stages followed similar tendencies, with a large number of intermediate products, along with compounds such as degraded proteins, peptides, and phenolic acids. The increased melanoidins gradually leads to darkening of garlic samples until dark brown or black color.…”
Section: Characteristic Components and Their Formation Mechanisms In Bgmentioning
confidence: 97%
“…Aged black garlic (ABG), an aged garlic preparation, is known as a functional food and is popular in Asia. ABG is produced by application of high temperature and humidity over 10 days [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. During the aging process, the odorous, harsh, and irritating compounds in fresh raw garlic (FRG) are converted naturally into stable and safe compounds [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the reduction in the intensities of the 2 strong peaks generated by exposure to 200 MPa for 25 min could only be partially compensated for by an increase in pressure up to 500 MPa. is same pattern was reflected across the total FT-IR spectrum and included the medium peak at 1417 (-CH) [16]. is pattern is indicative of a decrease in interchain interactions [26].…”
Section: Melanoidin Structural Alterations During Hhpmentioning
confidence: 83%
“…In these cases, the specific extinction coefficient (K mix ) is a unique identifier for melanoidins in mixtures. Absorption at 280 nm is primarily due to the presence of protein and phenolic acids, while 325 and 405 nm peaks can be attributed to the presence of phenolic acid-like compounds such as chlorogenic acid and melanoidins [16,17]. erefore, the K mix value at 280, 325, and 405 nm can provide information of the relative content of these compounds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation